Clinicopathologic characteristics and prognosis of Borrmann type IV gastric cancer: a meta-analysis - Luo, Yifan (World J Surg Oncol, 2016)
BACKGROUND: The clinicopathologic features and surgical treatment strategy of Borrmann type IV (B-4) gastric cancer remains controversial. This meta-analysis was conducted to evaluate the clinicopathologic features of patients with B-4 gastric cancer and to assess whether or not non-curative resection improved prognosis. METHODS: PubMed and Embase were searched for relevant articles. Statistical analysis was performed using RevMan (version 5.2). The odds ratio (OR), risk ratio (RR), hazard ratio (HR) with 95 % confidence interval (CI), and weighted average of median survival times were calculated as effect values. RESULTS: Fifteen studies were included. Compared with Borrmann type “others” (B-O), B-4 had a higher incidence of poorly differentiated carcinoma (OR = 4.92; 95 % CI = 3.10–7.83; P < 0.01), lymph node metastases (OR = 2.13; 95 % CI = 1.88–2.41; P < 0.01), peritoneal metastases (OR = 3.91; 95 % CI = 3.37–4.54; P < 0.01), serosal invasion (OR = 3.66; 95 % CI = 2.91–4.60; P < 0.01), and lymphatic invasion (OR = 1.39; 95 % CI = 1.02–1.91; P = 0.04). B-4 patients with non-curative resection were associated with a worse survival rate (HR = 2.83; 95 % CI = 2.35–3.40; P < 0.01) than patients with curative resection; however, B-4 patients with non-curative resection had a better survival rate (1-year: RR = 0.70, 95 % CI = 0.63–0.77; P < 0.01; 2-year: RR = 0.90, 95 % CI = 0.85–0.94; P < 0.01) than patients with non-resection. CONCLUSIONS: Our meta-analysis indicated that B-4 patients were associated with poor tumor differentiation, lymph node metastases, peritoneal metastases, serosal invasion, lymphatic invasion, and prognosis. Curative resection may increase the survival rate for B-4 patients. If it is not possible to perform a curative resection, a non-curative resection may improve the prognosis.